2014
DOI: 10.4236/jacen.2014.32b010
|View full text |Cite
|
Sign up to set email alerts
|

Crop Water Requirements in Egypt Using Remote Sensing Techniques

Abstract: The common Soil in Egypt is clay soil so common irrigation system is tradition surface irrigation with 60% irrigation efficiency. Agricultural sector consumes more than 80% of water resources under surface irrigation (tradition methods). In arid and semi-arid regions consumptive use is the best index for irrigation requirements. A large part of the irrigation water applied to farm land is consumed by Evapotranspiration (ET). Irrigation water consumption under each of the physical and climatic conditions for la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 12 publications
1
19
0
Order By: Relevance
“…This pattern reflects the typical growth pattern of winter wheat from anthesis to maturity [24]. For comparison, the maximum NDVI values in the Nile delta are 0.65-0.8 [25,26] and, thus, those in Dakhla are close to those in the Nile delta. In Dakhla, according to the interview results, winter crops (winter wheat or clover hay) are harvested in June.…”
Section: Seasonal Variation Of Ndvi In Government and Local Well Distmentioning
confidence: 51%
“…This pattern reflects the typical growth pattern of winter wheat from anthesis to maturity [24]. For comparison, the maximum NDVI values in the Nile delta are 0.65-0.8 [25,26] and, thus, those in Dakhla are close to those in the Nile delta. In Dakhla, according to the interview results, winter crops (winter wheat or clover hay) are harvested in June.…”
Section: Seasonal Variation Of Ndvi In Government and Local Well Distmentioning
confidence: 51%
“…Similarities between Kc curve and a satellite-derived vegetation index showed potential for modeling a Kc as a function of the vegetation index [21]. Therefore, the possibility of directly estimating Kc from satellite data was investigated [5] and [22] [23]. [5] represented the relation between Kc and NDVI through Equation 8which calibrated for wheat by [23].…”
Section: Eta and Etc Estimationmentioning
confidence: 99%
“…Therefore, the possibility of directly estimating Kc from satellite data was investigated [5] and [22] [23]. [5] represented the relation between Kc and NDVI through Equation 8which calibrated for wheat by [23].…”
Section: Eta and Etc Estimationmentioning
confidence: 99%
“…The highest governorate affected by climate change condition in water consumption of summer tomato was Behera while the lowest one was Minya governorate, and it"s worth to mentioning that water consumption of summer tomato in Upper Egypt governorates will decrease in 2020 and 2030 period and starting its effect by increase after 2030. Table ( 5) shows the water consumption of wheat during the seasons from (2011-2090) divided into averages each ten years of study period and it has been observed that, water consumption of wheat crop is increasing with The rate of change in wheat water consumption in relative to (2011-2020) period has been calculated and the result has been shown in figure (5) which indicated that, the water consumption of wheat crop will increase than base period in all studied governorates during study period except in Minya of 2060 decade which decrease its water consumption about 10% than base period. The rate of increment was lowest in 2050 decade where it has been ranged between 0 -2%, while it was the highest in 2080 decade and has been ranged between 7 -10% among the studied governorates.…”
Section: Results and Discussion:-evapotranspiration Values:-mentioning
confidence: 99%